2014
DOI: 10.1158/1078-0432.ccr-13-3060
|View full text |Cite
|
Sign up to set email alerts
|

FGFR1 mRNA and Protein Expression, not Gene Copy Number, Predict FGFR TKI Sensitivity across All Lung Cancer Histologies

Abstract: Purpose FGFR1 gene copy number (GCN) is being evaluated as a biomarker for FGFR tyrosine kinase inhibitor (TKI) response in squamous-cell lung cancers (SCC). The exclusive use of FGFR1 GCN for predicting FGFR TKI sensitivity assumes increased GCN is the only mechanism for biologically-relevant increases in FGFR1 signaling. Herein, we tested whether FGFR1 mRNA and protein expression may serve as better biomarkers of FGFR TKI sensitivity in lung cancer. Experimental Design Histologically diverse lung cancer ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
161
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(180 citation statements)
references
References 25 publications
19
161
0
Order By: Relevance
“…This phenomenon was evident for all analyzed Ewing sarcoma cell lines and was observed in vitro as well as in vivo. The efficacy of shRNA-based FGFR1 knockdown was far more prominent in Ewing sarcoma than in several other cancer types, such as lung cancer, which had previously been described to be associated with FGFR1 activity (42). Ponatinib as a FGFR1 inhibitor (39) showed significant activity toward proliferation of Ewing sarcoma cell lines in our experiments.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…This phenomenon was evident for all analyzed Ewing sarcoma cell lines and was observed in vitro as well as in vivo. The efficacy of shRNA-based FGFR1 knockdown was far more prominent in Ewing sarcoma than in several other cancer types, such as lung cancer, which had previously been described to be associated with FGFR1 activity (42). Ponatinib as a FGFR1 inhibitor (39) showed significant activity toward proliferation of Ewing sarcoma cell lines in our experiments.…”
Section: Discussionsupporting
confidence: 51%
“…Accordingly, FGFR1 was highly expressed on the protein level in almost all analyzed Ewing sarcoma. Gene amplification and overexpression are crucial pathogenetic mechanisms for growth factor receptors activation in multiple cancers (42,43). For example, EGFR amplification and overexpression with subsequent auto-activation has been described in breast cancer and lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We used validated models of FGFR1-amplified lung cancer: two squamous cell lines NCI-H520 and HCC95, and a small-cell lung cancer cell line DMS 114 (24), together with a non-amplified control squamous cell line HCC15 (29). Using Western blot analysis, we confirmed the presence of FGFR1 in all FGFR1-amplified lung cancer cell lines, whereas no detectable FGFR1 expression was observed in the HCC15 cell line (Fig.…”
Section: Internalization Of Scfvd2-fc Into Lung Cancer Cellsmentioning
confidence: 82%
“…According to recent studies, frequent amplification and overexpression of FGFR1 has been observed in tumor cells of a large proportion of squamous cell lung carcinoma patients (14,29) and a significant fraction of patients with small-cell lung cancer (17)(18)(19), while relatively little FGFR1 is found on non-tumor cells (42,43). Moreover, FGF receptors are localized to the plasma membrane which makes them accessible to various ligands coming from the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…The validity of the RNAScope system for semiquantitative assessment of mRNA in formalin fixed paraffin-embedded tissues has been shown previously by other groups. [12][13][14] In the tested samples, nonneoplastic liver was consistently negative suggesting very low or absent expression of PRKACA in normal liver. In endothelial cells and lymphocytes, ISH staining was limited, with only 1 þ expression (1 dot per cell) in lymphocytes and endothelial cells.…”
Section: Discussionmentioning
confidence: 99%